Comparação do desempenho muscular e proprioceptivo em jogadoras de voleibol e não atletas - Santos, Ricardo Cavalcante Oliveira (2010)
Introduction: The proprioception is a specialized variation of a sensorial modality and is divided into two modalities: joint position sense (JPS) and kinesthesia. The relation between shoulder proprioception and muscular performance has not been extensively studied in athletes participating in upper extremity sports. This evaluation should be important, since muscle activity balance is considered one component of the injury prevention in athletes. Purpose: To compare the muscular performance and shoulder proprioception between volleyball players and a control group. Methods: Twenty volleyball players aged between 15 and 22 years and twenty women non athletes were evaluated in three different ways. The first evaluation assessed the JPS, in which the participants should reproduce two target angles – 450 of medial rotation and 750 of lateral rotation – after a passive positioning. The second evaluation was the detection of passive motion in two different positions - shoulder neutral rotation and 750 of lateral rotation – and in direction to medial and lateral rotation. In this evaluation, the angular dislocation between the beginning of the movement and the perception was considered as the variable. The isokinetic concentric peak torque was the last evaluation, performed with five repetitions and a rest period between sets of 10 seconds. This evaluation considered two different velocities: 600/sec and 1800/sec and was performed in both lateral and medial rotators. Results: A significant difference was shown in the age, body mass and height between the participants (p<0.05). The volleyball players were younger, higher and had more body mass than the non athletes. Concentric peak torque at 1800/sec showed a significant difference, since the torque of the volleyball players was lower for both muscle groups – medial rotators (p=0.0443) and lateral rotators (p=0.0156). Conclusion: The participants evaluated showed difference in the muscular response of shoulder rotators in high velocities, although this was not observed in the proprioceptive response, maybe because the muscular training imposed to the athletes.